Does donor-recipient age mismatch have an influence on outcome after lung transplantation?: a single-centre experience - Franz, Maximilian; Aburahma, Khalil; Avsar, Murat; Boethig, Dietmar; Greer, Mark; Alhadidi, Hani; Sommer, Wiebke; Tudorache, Igor; Warnecke, Gregor; Haverich, Axel; Ius, Fabio; Salman, Jawad (European journal of cardio-thoracic surgery, 2023)
Lack of organ donors demands transplantation of older lung allografts for recipients between 0 and 50 years. So far, it has not yet been investigated whether donor-recipient age mismatch affects long-term outcome.Records of patients aged between 0 and 50 years were retrospectively reviewed. Donor-recipient age mismatch was calculated subtracting recipient age from donor age. Multivariable Cox regression analyses was performed to assess donor-recipient age mismatch regarding the end points’ overall patient mortality, mortality conditioned to hospital discharge, biopsy-confirmed rejection and chronic lung allograft dysfunction. Furthermore, we performed competing risk analysis to analyse if age mismatch affects biopsy-confirmed rejection and CLAD while death being a competing risk.Between January 2010 and September 2021, out of 1363 patients who underwent lung transplantation at our institution, 409 patients fulfilled the eligibility criteria and were included. Age mismatch ranged between 0 and 56 years. Multivariable analysis revealed that donor-recipient age mismatch does not affect overall patient mortality (P = 0.19), biopsy-confirmed rejection (P = 0.68) and chronic lung allograft dysfunction (P = 0.42). There was no difference seen in CLAD (P = 0.166) and biopsy-confirmed rejection (P = 0.944) with the competing risk death (P = 0.765 and P = 0.851; respectively).Age mismatch between recipients and donors of lung allografts does not affect long-term outcomes after lung transplantation.